Gender Stereotypes and Women's Participation in Leadership Positions at Mukono District Local Government - Amos Ongee (Uganda Christian University, 2023)
The study looked at how gender stereotypes affect the participation of women in leadership positionsin the Mukono District Local Government (MDLG). Its main objectives were to identify the prevalent gender preconceptions that have an impact on women's participation in leadership roles and to investigate how these stereotypes have affected women's engagement in leadership roles in Mukono District Local Government. The study was conducted utilizing a cross-sectional survey research design that also included qualitative and quantitative research methods. Both purposive and simple random sampling approaches were utilized to acquire the data through the use of questionnaires and interviews. The survey also included six department heads and a sample size of 80 respondents who are female employees of the Community Based Services Directorate at MDLG. The study findings highlighted the deeply entrenched gender stereotypes in MDLG that hinder women's progress in leadership. These stereotypes create a double bind, forcing women to navigate conflicting expectations and biases, limiting their access to support and fair treatment. This results in significant obstacles for women in attaining leadership roles and their underrepresentation in decision-making positions. Moreover, these stereotypes perpetuate a hostile work environment, raise legal and ethical concerns, and negatively impact team productivity and morale. Addressing these ingrained stereotypes is essential for promoting gender equality and fostering inclusive leadership in MDLG and similar organizations. Finally, the study recommended MDLG to take proactive measures, including regular gender sensitization workshops, mentorship programs, gender-neutral recruitment and promotion policies, safe reporting mechanisms, leadership training, promotion of inclusive leadership, and a commitment to gender equality. Additionally, public awareness campaigns should be initiated to challenge and change gender stereotypes in the broader community. These actions aim to foster a more inclusive and equitable work environment, empower women in leadership, and address the deeply rooted gender stereotypes identified in the study.
This is a dissertation.